Assessment of eye health care services of Bangladesh using eye care service assessment tools - Hussain, A.H.M. Enayet; Husain, Lutful; Roy, Abhijeet; Roy, Tapash; Islam, Rafiqul; Awlad Hossain, Mohammad; Ahmed, Munir (International Journal of Research in Medical Sciences, 2022)
Background: Bangladesh is being the commissioner for oaths to vision 2020, a global campaign for elimination of avoidable blindness by 2020, formulated a national eye care plan. This report illustrates the present status of Bangladesh eye health care service using eye care service assessment tool (ECSAT) that assesses an eye health system across six ‘building blocks’ of a health system. Methods: The study followed a mixed method to collect data. World health organization (WHO) standard ECSAT was used to gather information on eye care service. A purposive sampling method was used. Data from the assessment were extracted and all the information was cross-checked with leading stakeholders of ministry of health. Results: Eye care planning is led by the national eye care. There is a national eye health action plan and a national eye health coordination office under the ministry of health. The health delivery system includes primarily government and non-profit facilities with eight hospitals delivering specialist eye care services across the country. A significant proportion of eye care is provided through community outreach camps and a network of primary and community health workers. The national cataract surgical rate (CSR) is estimated at 2600 per million populations per year. Conclusions: This assessment suggests that although Bangladesh has made some progress towards elimination of avoidable blindness, it would be difficult to retain without further significant investment with a transparent accountability framework in eye health considering all limitation and contemporary challenges.